2016
DOI: 10.1007/s13762-016-1046-8
|View full text |Cite
|
Sign up to set email alerts
|

Performance of activated carbon-impregnated cellulose filters for indoor VOCs and dust control

Abstract: An activated carbon-impregnated cellulose filter was fabricated, and the capacity to remove dust and volatile organic compounds was evaluated in a laboratory. The adsorption capacities for benzene, toluene, ethyl benzene and m-xylene gases were compared by an adsorption isotherm test conducted as a preliminary test, showing that mxylene and benzene were the most and least favorable for adsorption onto activated carbon, respectively. Cellulose filters were made with four levels of activated carbon contents, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Moreover, the impregnation of cellulose filters with activated carbon was proposed as a good strategy to gain increased VOC removal ability. The example reported by Kim et al refers to an activated carbon cellulose filter with adsorption capacity for benzene, m-xylene, toluene, and methylbenzene [70].…”
Section: Membranes and Filmsmentioning
confidence: 99%
“…Moreover, the impregnation of cellulose filters with activated carbon was proposed as a good strategy to gain increased VOC removal ability. The example reported by Kim et al refers to an activated carbon cellulose filter with adsorption capacity for benzene, m-xylene, toluene, and methylbenzene [70].…”
Section: Membranes and Filmsmentioning
confidence: 99%
“…Kim et al developed an activated carbon-impregnated cellulose filter and used it to remove dust and volatile organic compounds (VOCs) in the laboratory. The results showed that the composite material had excellent adsorption capacity for PM 10 (99.7%), benzene, toluene, ethylbenzene, and m -xylene (98.9–100%) . However, the formation of a new filter material by a combination of nontoxic CFs and different MOF particles, which may represent a viable approach, is rarely reported, offering a new strategy to enhance the adsorption efficiency of toxic substances from the mainstream smoke.…”
Section: Introductionmentioning
confidence: 99%
“…Although hydrogen bonds are weaker than chemical bonds, they form long and numerous bonds, resulting in a strong binding force. Previous studies applied cellulose filters to remove particulate and gaseous contaminants in an indoor environment [26][27][28]. In addition, activated carbon was impregnated in cellulose filters to improve their adsorption efficiency of target contaminants.…”
Section: Introductionmentioning
confidence: 99%